Ovarian and peritoneal psammocarcinoma: Results of a multicenter study on 25 patients - Delhorme, Jean-Baptiste; Ohayon, Jordan; Gouy, Sébastien; Averous, Gerlinde; Genestie, Catherine; Gaichies, Léopold; Glehen, Olivier; Guilloit, Jean-Marc; Pezet, Denis; Quenet, Francois; Ferron, Gwenaël; Brigand, Cécile; et al. (European journal of surgical oncology, 2020)
Psammocarcinoma (PK) is a rare disease of unknown origin. We aimed to report the characteristics, management and survival of patients operated on for PK within the French Network for Rare Peritoneal Malignancies (RENAPE) expert centers. All consecutive cases of PK operated within all 26 RENAPE centers between 1997 and 2018 were retrospectively analyzed. Twenty-five patients were identified. The median age was 53 years [range 17–78]. None of the patients had extra peritoneal metastases at diagnosis. A median of 6 cycles of carboplatin-based systemic chemotherapy was delivered in 52% preoperatively (n = 13) and 56% postoperatively (n = 14); associated with placlitaxel for 12 patients. All patients were operated on. The median PCI was 23 [0–33]. Eighty-four percent had a complete cytoreductive surgery through digestive (n = 7), spleen (n = 3), pancreas (n = 1) resections and/or multiple peritonectomies (n = 11). Five patients (20%) had intraperitoneal chemotherapy. Morbidity (Dindo-Clavien ≥3) was 12%. No postoperative death occurred. After a median follow-up of 42 months (range [2–194]), the median overall (OS) and progression-free (DFS) survival times were respectively 128 months and 31 months. Eighteen patients recurred (72%), mainly in the peritoneum (n = 16). Four of them (22%) were reoperated. The 5 and 10-year DFS rates were both 20.3%. The 5 and 10-year OS rates were 62% and 51.7%, respectively. A complete cytoreductive surgery was associated with a better OS and DFS in a univariate analysis. Complete cytoreductive surgery is the cornerstone of the PK's management as a primary treatment. Recurrence remains common and new adjuvant strategies seem needed.